Pan-Africanism Reimagined II : FROM CONCEPTUAL BLUR TO OPERATIONAL BLUEPRINT - Nsiangani, Kibavuidi (USK Journal of Political Science and Epistemology, 2019)
This document serves as a foundational, non-normative synthesis, meticulously crafted to provide the core rationale and an overarching conceptual framework. It is intended to be the indispensable precursor for all subsequent normative works that will define the operational structure and strategic execution of a reimagined Pan-Africanism. Crucially, this text does not contain any formal conformance requirements; such mandatory specifications, standards, and implementation protocols will be exhaustively detailed in future, dedicated publications. This synthesis represents a comprehensive and expansive evolution of the principles first articulated in the landmark 2010 publication, Pan-Africanism Reimagined. It systematically integrates, refines, and significantly expands upon the concepts introduced therein, marking the successful completion of the first phase of the strategic roadmap. Its primary function is to constitute and launch the next, critical phase of this established roadmap: the transition from theory to actionable strategy. The ultimate and overarching goal of this phase is to fully operationalize Pan-Africanism, establishing it not merely as a philosophical ideal but as a cohesive, coherent, and practical strategic doctrine for the 21st century. This doctrine is designed to guide coordinated action across the continent and the diaspora in areas of security, economic integration, political cooperation, and cultural renaissance.
Implementation Manual: Operational Definitions, Auditability, and Sovereignty function, Anti-Capture Design